From transliteration to trans-scripting: Creativity and multilingual writing on the internet. (June 2019) - Spilioti, Tereza
Highlights: Trans-scripting refers to processes of respelling that are creative and performative. Social media users manipulate Greek characters to respell English-related forms. Orality plays a key role in creative play with written form and trans-scripting online. Respellings of English-related forms become resources for metalinguistic commentary. Abstract: Although research on multilingual writing has widely explored transliteration and, particularly, Romanization practices, we know little about how related phenomena are reconfigured in social media contexts where users can manipulate a wide range of writing resources and navigate between multiple intertwining audiences. By analysing more than one thousand tokens of forms that illustrate what appears as reversed Romanization (i.e. English-related forms written with Greek characters, engreek ), the study aims to discover, first, how these forms are created and, second, for what purposes, and for whom, they are mobilised at given moments. In order to address these questions, I propose a translanguaging lens for the study of multilingual digital writing and draw on the notion of trans-scripting as key for understanding such writing practices as creative and performative. My findings reveal that there is a link between trans-scripting as a creative practice and digital orality, as users orient primarily to phonetic respellings of the English-related forms and associate such spellings with particular forms of stylized speech and social personas. The paper concludes with a critical discussion of the study's implications to research on the role of English as a resource for multilingual writing and current debates about language diversity and fluidity in the digital mediascape.